Poor-In-World or World-Forming? Rethinking the Heideggarian Notion of Animality [¿Pobres y Ricos de Mundo? Repensando la Noción Heideggeriana de la Animalidad] - Neira-Barrera, H (Pontificia Universidade Catolica do Parana, 2014)
Heidegger creates the idea that the animal is "poor-in-world", conversely to the Dasein, which is "world-forming". On this difference between animals and the Dasein it is possible to present two hypothesis: if the distinction is merely descriptive, it does not imply a hierarchy of the human over the animal. If, instead, in Heidegger s description are mixed some worth aspects or if he adds some aspects (not necessarily explicit) of domination of the human on the animal, then Heidegger reestablishes some traits of animal metaphysics, what is contrary to his aim of questioning metaphysics. The result of this proceeding would be, also, to recompose some aspects of metaphysics of the human. To what extent and why Heidegger s conception of the human being as Dasein or "world-forming", or of animal as an "poor-inworld" entity, represents a meaningful contribution to a research which thinks the limits and range of the relation man-animal-world? And which are some of the consequences one could deduce if in the Heideggerian description of the subject arise some normative issues, not forseen by the German philosopher?